(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The scientific article discusses the results of a laboratory study of the effect of various concentrations of humatedorgano-mineral fertilizer obtained from oxidized brown coals of Kyrgyzstan on the growth and development of a plant: tomato and bell pepper.